Pelestarian dan Strategi Pengembangan Stasiun Kereta Api sebagai Bangunan Cagar Budaya di Kota Medan - Azizah, Siti Nur; Pratama, Dino; Aziz, Filza Shaluza Shavifa; Candylian, Nayla; Afani, Tasya; Nuraini, Cut (PT. Arsil Reka Engineering, 2025)
This study examines the heritage significance and development strategy of Medan Railway Station, a colonial-era transportation building constructed in 1883 by Deli Spoorweg Maatschappij (DSM), a private railway company operating during the Dutch colonial period, and used to transport tobacco and rubber from plantation areas to the port. Using a descriptive-qualitative approach combining field observation, visual documentation, and literature review, this research examines the station's historical, architectural, social, and educational values, and formulates a development strategy through SWOT analysis. Findings show that although the building's clock tower and several colonial structural elements are preserved, the station has undergone extensive renovation, most significantly since 2013 with the addition of a modern glass-and-steel City Railway Station building, resulting in substantial loss of the original colonial architectural character. The remaining preserved elements, including the clock tower, platform roof, and depot structures, function as physical evidence of the colonial transportation era. The SWOT analysis identifies the station's strategic central location and integrated transport modes as key strengths, limited parking and uneven accessibility as weaknesses, growing public transport demand and digital technology as opportunities, and competition from online transportation and private vehicles as the main threats. These findings support heritage-sensitive management strategies that balance the station's continued operational function with the preservation of its remaining colonial architectural identity.